Grief Of Louis Creed In Stephen King’s Pet Sematary - Palandi, Richi Junior; Wuntu, Ceisy N.; Andries, Fivy (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This research explores the psychological transformation of Louis Creed, the protagonist in Stephen King’s Pet Sematary, through the lens of the Dual Process Model of Coping with Bereavement developed by Stroebe and Schut (1999). The study aims to analyze how grief and loss shape Louis’s character, behavior, and moral decisions throughout the novel. By examining his response to the death of his son and his subsequent descent into denial and irrationality, this research reveals a failure to oscillate between the two critical coping mechanisms proposed in the model: loss-oriented and restoration-oriented coping. The analysis demonstrates that Louis becomes trapped in grief and unable to adapt to life after loss, ultimately leading to psychological collapse and catastrophic outcomes. Supporting evidence is drawn from key scenes and direct quotations from the novel. This study not only contributes to literary character analysis but also highlights the relevance of psychological frameworks in understanding human responses to trauma and bereavement